The rising entropy of English in the attention economy - Pilgrim, Charlie; Guo, Weisi; Hills, Thomas T. (Springer, 2024)
We present evidence that the word entropy of American English has been rising steadily since around 1900. We also find differences in word entropy between media categories, with short-form media such as news and magazines having higher entropy than long-form media, and social media feeds having higher entropy still. To explain these results we develop an ecological model of the attention economy that combines ideas from Zipf’s law and information foraging. In this model, media consumers maximize information utility rate taking into account the costs of information search, while media producers adapt to technologies that reduce search costs, driving them to generate higher entropy content in increasingly shorter formats.
Keywords: 4701 Communication and Media Studies; 47 Language, Communication and Culture